Onecut Regulates Core Components of the Molecular Machinery for Neurotransmission in Photoreceptor Differentiation - Vassalli, Quirino Attilio; Colantuono, Chiara; Nittoli, Valeria; Ferraioli, Anna; Fasano, Giulia; Berruto, Federica; Chiusano, Maria Luisa; Kelsh, Robert Neil; Sordino, Paolo; Locascio, Annamaria (Frontiers in Cell and Developmental Biology, 2021)
Photoreceptors (PRC) are neurons highly specialized for sensing light stimuli and have considerably diversified during evolution. The genetic mechanisms that underlie photoreceptor differentiation and accompanied the progressive increase in complexity and diversification of this sensory cell type are a matter of great interest in the field. A role of the homeodomain transcription factor Onecut (Oc) in photoreceptor cell formation is proposed throughout multicellular organisms. However, knowledge of the identity of the Oc downstream-acting factors that mediate specific tasks in the differentiation of the PRCs remains limited. Here we used transgenic perturbation of the Ciona robusta Oc protein to show its requirement for ciliary PRC differentiation. Then, transcriptome profiling between the trans-activation and trans-repression Oc phenotypes identified differentially expressed genes that are enriched in exocytosis, calcium homeostasis and neurotransmission. Finally, comparison of RNA-Seq datasets in Ciona and mouse identifies a set of Oc downstream genes conserved between tunicates and vertebrates. The transcription factor Oc emerges as a key regulator of neurotransmission in retinal cell types.